Preparation method and application of electrode material for low-temperature zinc ion battery

By coupling the preparation of V2O5/nanoflower-like porous carbon composite, the problem of insufficient performance of the V2O5 cathode material under low temperature conditions is solved, efficient and stable zinc ion battery performance is achieved, and its application range is expanded.

CN119612500AActive Publication Date: 2025-03-14YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411803828.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

When used alone, existing V2O5 cathode materials have problems such as poor conductivity and ionic conductivity, slow electrolyte transmission rate, and poor stability, which are difficult to effectively apply under low temperature conditions.

Method used

The V2O5/nanoflower-like porous carbon-based zinc ion cathode material was prepared by coupling strategy. By optimizing the pore structure of the carbon particles on the surface of the nanoflower-like carbon surface and covering it with vanadium pentoxide hydrothermal covering it, the composite material was formed to improve the conductivity and cyclic stability of the electrode.

Benefits of technology

It realizes high-efficiency zinc ion battery performance under low temperature conditions, including high specific capacity, long cycle life and excellent low temperature performance, significantly improving the electrochemical performance and application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612500A_ABST
    Figure CN119612500A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy zinc-vanadium battery materials, in particular to a preparation method and application of an electrode material for a low-temperature zinc ion battery. The method comprises the following steps: mixing cobalt acetylacetonate, water and furfural, and sequentially carrying out heat treatment and centrifugation to obtain a precipitate; mixing the precipitate with a potassium hydroxide solution, and calcining for the first time to obtain a calcined material; mixing the calcined material with ammonium metavanadate and water, and sequentially carrying out hydrothermal treatment and drying to obtain a dried material; and calcining the dried material for the second time to obtain the electrode material. The V2O5 / nano flower-shaped porous carbon-based zinc ion cathode material is prepared by adopting a coupling strategy and shows relatively good cycling stability in a zinc ion battery, and more channels exist on the surface of the carbon material, so that rapid diffusion of zinc ions is promoted, the conductivity and the ionic conductivity are improved, and application at low temperature is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy zinc-vanadium battery materials, and in particular to a method for preparing an electrode material for a low-temperature zinc ion battery and an application thereof. Background Art

[0002] Among various energy storage devices, lithium-ion batteries (LIBs) have important application value in portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, flammable organic electrolytes, scarce lithium resources, and high costs have seriously hindered the application of lithium-ion batteries as large-scale energy storage systems. In order to achieve the goal of high safety and low cost of rechargeable batteries, more research is focused on aqueous batteries, including aqueous lithium-ion batteries, aqueous sodium-ion batteries, vanadium flow batteries, and Zn-Br2 batteries. As an aqueous battery material, zinc has a high energy density of up to 820 mAh g -1 The theoretical specific capacity and low equilibrium redox potential (-0.76 V) make it a promising candidate for aqueous zinc-ion batteries (ZIBs). In addition, zinc is cheap, abundant and environmentally friendly.

[0003] As with other batteries, the electrode materials and their properties of zinc-ion batteries are the key to improving battery performance. Currently, the focus of research is on how to improve the efficient and rapid insertion / extraction of divalent zinc ions within the framework of positive electrode materials to obtain higher electrochemical performance. To date, various compounds have been used as cathodes for ZIBs, including manganese-based oxides, vanadium-based oxides, Prussian blue analogs, and organic conductive polymers. Among them, ZIBs with multiple oxidation states (V 2+ 、V 3+ 、V 4+ 、V 5+ ) and vanadium-based oxides with an open framework crystal structure have high theoretical capacity and good cycle stability. Since the V2O5 cathode has a high specific capacity (589 mAh g -1 ), so V2O5 cathode has been widely studied for the preparation of aqueous zinc-ion batteries. Although V2O5 is an excellent electrode material, when V2O5 is used alone as a cathode, there are problems such as poor electrical conductivity and ionic conductivity, slow electrolyte transfer rate, and poor stability. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing an electrode material for a low-temperature zinc ion battery and an application thereof. The present invention adopts a coupling strategy to prepare a V2O5 / nanoflower-shaped porous carbon-based zinc ion cathode material, which exhibits good cycle stability in a zinc ion battery because there are more channels on the surface of the carbon material, which promotes the rapid diffusion of zinc ions, thereby improving the conductivity of the electrode and realizing application at low temperatures.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an electrode material for a low-temperature zinc ion battery, comprising the following steps:

[0007] 1) mixing cobalt acetylacetonate, water and furfural, and then sequentially performing heat treatment and centrifugation to obtain a precipitate;

[0008] 2) mixing the precipitate obtained in step 1) with potassium hydroxide and water and then calcining it for the first time to obtain a calcined material;

[0009] The temperature of the first calcination is 650-850°C;

[0010] 3) mixing the calcined material obtained in step 2) with ammonium metavanadate and water, and then performing hydrothermal treatment and drying in sequence to obtain a dried material;

[0011] The temperature of the hydrothermal treatment is 160-200°C and the time is 12h;

[0012] 4) calcining the dried material obtained in step 3) for a second time to obtain an electrode material;

[0013] The second calcination was carried out at a temperature of 400° C. and for 30 minutes.

[0014] Preferably, the temperature of the hydrothermal treatment in step 3) is 180°C.

[0015] Preferably, in step 1), the mass ratio of cobalt acetylacetonate, furfural and water is 0.8:0.3:40.

[0016] Preferably, the heat treatment conditions in step 1) include: temperature of 180° C. and time of 16 h.

[0017] Preferably, the mass ratio of the precipitate in step 2) to potassium hydroxide and water is 4:1:10.

[0018] Preferably, the conditions of the first calcination in step 2) further include: calcining for 1 hour under a nitrogen atmosphere.

[0019] Preferably, the mass ratio of the calcined material in step 3) to the mass ratio of ammonium metavanadate and water is 1:2:40;

[0020] The drying conditions include: temperature of 60° C. and time of 12 h.

[0021] The present invention also provides an electrode material for a low-temperature zinc ion battery prepared by the preparation method described in the above technical solution.

[0022] The present invention also provides the use of the electrode material described in the above technical solution in the preparation of a low-temperature zinc ion battery.

[0023] The present invention also provides a low-temperature zinc ion battery, comprising a zinc foil anode and a cathode;

[0024] The cathode is prepared from the electrode material described in the above technical solution, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone;

[0025] The volume ratio of the mass of the electrode material, the mass of acetylene black, the mass of polyvinylidene fluoride and N-methylpyrrolidone is 70 mg:20 mg:10 mg:150 μL.

[0026] Beneficial effects of the present invention:

[0027] The present invention optimizes the surface pore structure of carbon particles by a one-step KOH activation method, and hydrothermally covers the surface of nanoflower-like carbon with vanadium pentoxide to obtain a V2O5 / nanoflower-like porous carbon composite material. Through data comparison, the composite material has interface coupling and efficient transport characteristics, which can effectively increase the interlayer spacing and realize the hydrated Zn 2+ The rapid and reversible insertion / extraction of the electrochemical device improves the cycling stability and enhances the electrochemical performance, thus expanding its application range. -1 The reversible specific capacity of the V2O5-180 cathode material is 244.4 mAh g -1 , energy density is 171Wh kg -1 After 7000 cycles, V2O5-180 still maintains 92% of its original specific capacity and nearly 98% of its Coulombic efficiency. In addition, the assembled zinc-vanadium battery has excellent low-temperature performance and operability, with a specific capacity value of 171 mAh g at -20 °C. -1 , with a specific capacity retention of 70% and good electrochemical reversibility. This coupling approach promotes the diffusion or transport of multivalent ions, providing hope for the fabrication of next-generation water-rechargeable zinc-ion energy storage devices.

[0028] 1. V2O5 / nanoflower-like porous carbon-based zinc ion cathode material was prepared by coupling strategy.

[0029] 2. Excellent energy storage performance, including a current density of 50mA g -1 High capacity (244.35mAh g -1 ) and high energy density (171Wh kg -1 ).

[0030] 3. Satisfactory cycle stability, with a cycle number of up to 7,000 times and a capacity retention rate of 92%.

[0031] 4. High current density and low temperature applications (specific capacity value is 171mAh g -1 , the specific capacity retention rate is 70% at -20℃). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0033] Figure 1 SEM images of nano-flower-like carbon particles at different activation temperatures;

[0034] Figure 2 Wide-angle XRD patterns of samples at different hydrothermal temperatures;

[0035] Figure 3 The current density is 0.05Ag -1 GCD curves of different samples;

[0036] Figure 4 For V2O5-180 at 1.0Ag -1 Stability and Coulombic efficiency for 7000 cycles under 24-hour conditions;

[0037] Figure 5 This is the rate performance of V2O5-180 at different temperatures and current densities. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing an electrode material for a low-temperature zinc ion battery, comprising the following steps:

[0039] 1) mixing cobalt acetylacetonate, water and furfural, and then sequentially performing heat treatment and centrifugation to obtain a precipitate;

[0040] 2) mixing the precipitate obtained in step 1) with potassium hydroxide and water and then calcining it for the first time to obtain a calcined material;

[0041] The temperature of the first calcination is 650-850°C;

[0042] 3) mixing the calcined material obtained in step 2) with ammonium metavanadate and water, and then performing hydrothermal treatment and drying in sequence to obtain a dried material;

[0043] The temperature of the hydrothermal treatment is 160-200°C and the time is 12h;

[0044] 4) calcining the dried material obtained in step 3) for a second time to obtain an electrode material;

[0045] The temperature of the second calcination is 400°C.

[0046] The present invention mixes cobalt acetylacetonate, water and furfural, and then sequentially performs heat treatment and centrifugation to obtain a precipitate. In the present invention, the mass ratio of the cobalt acetylacetonate, furfural and water is preferably 0.8:0.3:40. In the present invention, the heat treatment conditions preferably include: a temperature of 180°C and a time of 16 hours.

[0047] The present invention mixes the obtained precipitate with potassium hydroxide solution and then performs a first calcination to obtain a calcined material; the temperature of the first calcination is 650-850°C. In the present invention, the precipitate is mixed with potassium hydroxide and water in a mass ratio of 4:1:10. In the present invention, the conditions of the first calcination also preferably include: calcining for 1 hour under a nitrogen atmosphere.

[0048] The present invention mixes the obtained calcined material with ammonium metavanadate and water, and then performs hydrothermal treatment and drying in sequence to obtain a dried material; the temperature of the hydrothermal treatment is 160-200°C and the time is 12 hours. In the present invention, the temperature of the hydrothermal treatment is preferably 180°C. In the present invention, the mass ratio of the calcined material to the mass ratio of ammonium metavanadate and water is 1:2:40. In the present invention, the drying conditions preferably include: a temperature of 60°C and a time of 12 hours.

[0049] The present invention performs a second calcination on the obtained dried material to obtain the electrode material; the temperature of the second calcination is 400° C. and the time is 30 minutes.

[0050] In the present invention, furfural, cobalt acetylacetonate, potassium hydroxide, ammonium metavanadate, and zinc perchlorate were purchased from Aladdin (Shanghai, China). All chemicals were used as received without further purification.

[0051] The present invention also provides an electrode material for a low-temperature zinc ion battery prepared by the preparation method described in the above technical solution.

[0052] The present invention also provides the use of the electrode material described in the above technical solution in the preparation of a low-temperature zinc ion battery.

[0053] The present invention also provides a low-temperature zinc ion battery, comprising a zinc foil anode and a cathode; the cathode is prepared from the electrode material described in the above technical solution, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone; the volume ratio of the mass of the electrode material, the mass of acetylene black, the mass of polyvinylidene fluoride and N-methylpyrrolidone is 70mg:20mg:10mg:150μL.

[0054] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0055] Example 1

[0056] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0057] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 650°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0058] Example 2

[0059] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0060] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 750°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0061] Example 3

[0062] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0063] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 850°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0064] Example 4

[0065] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0066] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 750°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0067] Then add 0.0025 mol of ammonium metavanadate and 0.14625 g of activated sample into 40 ml of water, heat with stirring for 30 min, then set the hydrothermal temperature at 160°C for 12 h, put it into a vacuum drying oven, heat at 60°C for 12 h, and calcine at 400°C for 30 min in an air atmosphere to obtain a V2O5-coated nanoflower-like porous carbon composite material, which is calculated as V2O5-160.

[0068] Example 5

[0069] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0070] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 750°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0071] Then add 0.0025 mol of ammonium metavanadate and 0.14625 g of activated sample into 40 ml of water, heat with stirring for 30 min, then set the hydrothermal temperature at 180°C for 12 h, put it into a vacuum drying oven, heat at 60°C for 12 h, and calcine at 400°C for 30 min in an air atmosphere to obtain a V2O5-coated nanoflower-like porous carbon composite material, which is calculated as V2O5-180.

[0072] Example 6

[0073] 0.8 g of cobalt acetylacetonate was dissolved in 40 ml of water and stirred at 80° C. for at least 5 minutes. 0.3 g of furfural was continuously stirred with the dissolved cobalt acetylacetonate solution until fully mixed, and hydrothermally treated at 180° C. for 16 h, and the solid sample was centrifuged at 4000 r / min.

[0074] The sample was mixed with potassium hydroxide and water in a mass ratio of 4:1:10. The mixture was then calcined at 750°C for 1 h under a N2 atmosphere at a heating rate to obtain an activated sample.

[0075] Then add 0.0025 mol of ammonium metavanadate and 0.14625 g of activated sample into 40 ml of water, heat with stirring for 30 min, then set the hydrothermal temperature at 200 °C for 12 h, put it into a vacuum drying oven, heat at 60 °C for 12 h, and calcine at 400 °C for 30 min in an air atmosphere to obtain a V2O5-coated nanoflower-like porous carbon composite material, calculated as V2O5-200.

[0076] Comparative Example 1

[0077] The sample not activated by the activator in Example 2 was named V2O5-NO, and the amorphous carbon sample not activated by the activator in Example 2 was named V2O5-C.

[0078] Material characterization tests:

[0079] The morphology of the samples was measured using a field emission scanning electron microscope (SEM, Thermo Scientific, USA) at an operating voltage of 100 kV. The crystal phase analysis of the prepared materials was performed using a wide-angle X-ray diffractometer (XRD, PANalytical BV, The Netherlands) with a Ni-filtered Cu-Ka radiation source on an X'Pert PRO MPD X-ray diffractometer.

[0080] Electrochemical characterization tests:

[0081] The mass of V2O5-x, the mass of acetylene black, the mass of polyvinylidene fluoride (PVDF), and the mass of N-methylpyrrolidone (NMP) were mixed in a ratio of 70mg:20mg:10mg:150μL, and then the slurry was scraped onto a stainless steel sheet with a preparation device to a thickness of 300μm. After drying in a vacuum oven at 80℃ for 12h, the stainless steel sheet was cut into a circular electrode sheet with a diameter of 14mm using a slicer.

[0082] The electrochemical performance test was carried out using a CR2032 button cell. The CR2032 button cell consists of a zinc foil anode (100 μm, polished with fine-grained sandpaper) and a V2O5-x cathode, and the electrolyte is 3 M Zn(C1O4)2. The constant current charge and discharge test (GCD) was carried out on a CHI660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., China). The GCD test current density was 0.05-1Ag -1 , the potential window is 0.2~1.6V(vs.Zn 2+ / Zn). The cycling stability tests were performed on a Land CT2001A battery testing system (Wuhan, China).

[0083] Performance Testing:

[0084] Firstly, a one-step hydrothermal method was used to synthesize nanoflower-like spherical carbon particles, such as Figure 1 As shown, the carbon particles are uniform in size (about 5 μm in diameter) and have a petal-like surface. In order to further improve the pore structure of the carbon material, the pore structure was adjusted by calcining KOH at different activation temperatures. Figure 1 Figures a, b, and c are SEM images of nanoflower-like carbon particles at different activation temperatures of 650°C, 750°C, and 850°C. Figure 1 Middle (d), the nanoflower-like structure on the surface of the carbon particle is assembled from lamellar structural units with a thickness of about 150 nm, and the surface is slightly etched by KOH.

[0085] Figure 2 The XRD spectra of the samples at different hydrothermal temperatures are shown in Figure 2. The characteristic peak diffraction angles of the materials prepared at different hydrothermal temperatures are 21.70, 26.3, and 45.4°, respectively, corresponding to the (110), (101), and (411) crystal planes of cubic V2O5 (PDF#41-1426). The results show that orthorhombic vanadium pentoxide was successfully synthesized. According to the Bragg equation, the d-spacings of the (110) and (101) peaks are approximately 4.2 angstroms and 3.4 angstroms, respectively. The d-spacing of the (101) peak is due to the diffraction of amorphous carbon (002) V2O5-C. At high temperatures, when the nanoflower-like porous carbon is composited with V2O5, the interlayer spacing increases. With the increase of the hydrothermal temperature, the diffraction peaks of V2O5-200 gradually broaden, indicating that its crystallinity is relatively poor.

[0086] Depend on Figure 3 It can be seen that the GCD curves of different samples at different hydrothermal temperatures are almost symmetrical, indicating that the electrode material has good electrochemical reversibility. The specific capacity values ​​of samples V2O5-C, V2O5-NO, V2O5-160 and V2O5-200 are 54.5, 95, 152.4 and 122.3 mAh g -1 The charge and discharge time of sample V2O5-180 is significantly longer, indicating that it has the highest specific capacity value, with a discharge capacity of up to 244.4 mAh g -1 .

[0087] like Figure 4 As shown, at 1.0A g -1 The stability and coulombic efficiency of V2O5-180 were tested for 7000 cycles under the same current density. After 7000 cycles, V2O5-180 still maintained 92% of its original specific capacity and the coulombic efficiency was close to 98%, indicating that V2O5-180 has good electrochemical variability and excellent cycle stability as an electrode material.

[0088] like Figure 5 As shown in the figure, the specific capacity of the prepared V2O5-180 is 171 mAh g at -20 °C. -1 , the specific capacity retention rate is 70%, indicating that the interlayer spacing of the V2O5-180 composite material can adjust the Zn 2+ storage capacity, while larger pore size and interlayer spacing increase ion diffusion and Zn 2+ Storage dynamics.

[0089] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an electrode material for a low-temperature zinc ion battery, characterized in that: The following steps are involved: 1) mixing cobalt acetylacetonate, water and furfural, and then sequentially performing heat treatment and centrifugation to obtain a precipitate; 2) mixing the precipitate obtained in step 1) with potassium hydroxide and water and then calcining it for the first time to obtain a calcined material; The temperature of the first calcination is 650-850°C; 3) mixing the calcined material obtained in step 2) with ammonium metavanadate and water, and then performing hydrothermal treatment and drying in sequence to obtain a dried material; The temperature of the hydrothermal treatment is 160-200°C and the time is 12h; 4) calcining the dried material obtained in step 3) for a second time to obtain an electrode material; The second calcination was carried out at a temperature of 400° C. and for 30 minutes.

2. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step 3) is 180°C.

3. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of cobalt acetylacetonate, furfural and water is 0.8:0.3:

40.

4. The preparation method according to claim 1, characterized in that: The conditions of the heat treatment in step 1) include: temperature of 180° C. and time of 16 hours.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the precipitate to potassium hydroxide and water in step 2) is 4:1:

10.

6. The preparation method according to claim 1, characterized in that: The conditions of the first calcination in step 2) also include: calcination for 1 hour under a nitrogen atmosphere.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the calcined material to the ammonium metavanadate and water in step 3) is 1:2:40; The drying conditions include: temperature of 60° C. and time of 12 h.

8. An electrode material for a low-temperature zinc ion battery prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the electrode material according to claim 8 in preparing a low-temperature zinc ion battery.

10. A low temperature zinc ion battery, characterized in that Includes zinc foil anode and cathode; The cathode is prepared from the electrode material according to claim 7, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone; The volume ratio of the mass of the electrode material, the mass of acetylene black, the mass of polyvinylidene fluoride and N-methylpyrrolidone is 70 mg:20 mg:10 mg:150 μL.

Citation Information

Patent Citations

  • Vanadium pentoxide / hawthorn-based porous carbon composite material as well as preparation method and application thereof

    CN111710536A

  • Method for mechanochemical activation of water-based zinc ion battery positive electrode material and application of water-based zinc ion battery positive electrode material

    CN119029165A

  • Permanent magnet modules for an electric machine

    KR1020200031030A

  • V 2o 5 hollow micron wire ball with nanowire three-dimensional winding structure and preparation method therefor and use thereof

    WO2017036069A1